Determination of anticancer activity of several Vietnamese plant extracts by employing the in-vitro bioassay system - Thao, Do Thi; Phuong, Do Thi; Hieu, Nguyen Khac; Hung, Nguyen Van (Academia Journal of Biology, 2014)
Determination of anticancer activity of several Vietnamese plant extracts by employing the in-vitro bioassay system